The effects of tennis on depressive symptoms and pro-social behaviors in university students: the mediating role of appreciative social support - Sun, Runjuan; Li, Tianpei; Li, Mingyuan; Meng, Liang (Frontiers in Psychology, 2025)
AimsThis research aimed to explore the impact of tennis on depressive symptoms and pro-social behaviors among college students, while also delving into the intermediary function of social support navigation.Materials and methodsUtilizing a suite of psychological evaluations and social support instruments, the study compared the levels of depressive symptoms and pro-social behaviors between collegiate tennis athletes and their non-athlete peers.ResultsThe findings revealed an inverse relationship between the duration of tennis engagement and the presence of depressive symptoms (β = −0.234, p <0.001), alongside a direct positive association with pro-social tendencies (β = 0.222, p < 0.001). Further scrutiny uncovered a substantial link between the degree to which participants valued social support and their experiences of depressive symptoms (indirect effect = −0.212, 95%CI = −0.036 ~ −0.009) and pro-social behaviors (indirect effect = 0.025, 95%CI = 0.009 ~ 0.044). Notably, the valuation of social support served as a conduit for the beneficial effects of tennis on these outcomes within the collegiate population. Consequently, the evidence from this investigation underscores the salutary influence of tennis on the psychological well-being and social conduct of college students, highlighting the pivotal role of understanding and leveraging social support.ConclusionThese insights offer valuable direction for fostering mental health and social proficiency in the university setting and advocate for the integration of sports as a viable component in mental health strategies.